Monsters, mutants and missing links the real science behind the X-files - Simon, Anne (Ebury Press, 1999)
Dr Anne Simon is a world-renowned biologist and expert on plant viruses. She has also been scientific advisor to the "X-Files" TV programme since the series began. In this volume she explores the realities that lie behind the discoveries made in each episode by Mulder and Scully.